Impacts of Extreme Weather on Sea Surface Temperature in the Western Waters of Sumatera and the Southern Waters of Java in June 2016 - Martono Martono (Forum Geografi, 2017)
Ocean dynamics is affected by atmospheric conditions. Surface wind is one of atmospheric variables that has an important role in the ocean dynamics. This study was conducted to determine impacts of extreme weather on sea surface temperature in the western waters of Sumatera and the southern waters of Java in June 2016. Daily surface wind (2007-2016), sea surface temperature (1987-2016), sea wave height (1-10 June 2016) and surface current (1994-2016) were analyzed using anomaly analysis to assess the impact of surface winds on surface ocean. The result showed that in June 2016 extreme weather occurred in these waters that was characterized by sea wave height reached 2.6 m. Impacts of extreme weather in these waters cause upwelling intensity weakened that was marked by increase of sea surface temperature. The increases of sea surface temperature in the middle to north of western waters of Sumatera reached 0.9 OC, in the middle to south of western waters of Sumatera reached 1.8 OC and in the southern waters of Java reached 1.6 OC.